2011
DOI: 10.1021/jf200183m
|View full text |Cite
|
Sign up to set email alerts
|

Lunasin and Bowman-Birk Protease Inhibitor Concentrations of Protein Extracts from Enzyme-Assisted Aqueous Extraction of Soybeans

Abstract: Lunasin and Bowman-Birk protease inhibitor (BBI) are two soybean peptides to which health-promoting properties have been attributed. Concentrations of these peptides were determined in skim fractions produced by enzyme-assisted aqueous extraction processing (EAEP) of extruded full-fat soybean flakes (an alternative to extracting oil from soybeans with hexane) and compared with similar extracts from hexanedefatted soybean meal. Oil and protein were extracted by using countercurrent twostage EAEP of soybeans at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Surprisingly, the advancement of recombinant antibody technology is under-represented in food research and industry, an area where there is a need for improved analytical and purification methodologies. 22,31 Just as soy consumption patterns vary greatly across the world, so too do cancer incidences. An inverse relationship between soybean intake and cancer incidence has been reported, with Asian countries where soy forms an important part of the diet, such as Japan, displaying the lowest incidences of cancer.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the advancement of recombinant antibody technology is under-represented in food research and industry, an area where there is a need for improved analytical and purification methodologies. 22,31 Just as soy consumption patterns vary greatly across the world, so too do cancer incidences. An inverse relationship between soybean intake and cancer incidence has been reported, with Asian countries where soy forms an important part of the diet, such as Japan, displaying the lowest incidences of cancer.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The propensity for BBI to self-associate has previously been observed by us and others, with or without SDS, and in the presence of β-mercaptoethanol and urea. 3,9,31 After separation on the SDS-PAGE gel, proteins immunoprecipitated by magnetic particles were then analyzed by direct tandem mass spectrometry after in-gel digestion with trypsin and reversephase separation of the tryptic peptides. The prominent band was identified as the soybean trypsin inhibitor (Figure 6b).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the AEP section, the comparison of our results with the literature is challenging due to the lack of studies reporting oil and protein extraction yields from partially defatted almond cake produced by mechanical pressing. For example, while oil extraction yields ranging from 75-78% have been reported for the EAEP of full-fat almond flour [12,53], no protein extraction yields were reported for both studies. Because of the difference in the starting material used (full fat almond flour vs. partially defatted almond cake), a direct comparison of the results from both studies is difficult.…”
Section: Enzyme-assisted Aqueous Extraction Process Of Almond Cake: Pmentioning
confidence: 91%
“…Moreover, studies in animals showed that lunasin can be administered orally and can enter target tissues (de Lumen, 2005). Findings that lunasin is bioavailable, bioactive and thermostable after administration provided the basis for recommendations of the inclusion of lunasin-containing products in regular human diets (Leite Nobrega de Moura et al, 2011;Park et al, 2007;Jeong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%